A comparative study of administrative organization and financing of the public elementary and secondary schools in the Philippines and Thailand - Umpray, Kiat 1940- (s.n.], 1971)
This study presented a comparison of the organization, administration, and financing programs of public elementary and general secondary schools in the Philippines and in Thailand. In general, there are more differences than similarities in the organization, administration, and financing of public elementary and general secondary schools of the Philippines and Thailand.